A Case of Liposarcoma With Peritonitis Due to Jejunal Perforation. (2003) - Horiguchi, Hisashi; Matsui, Miwa; Yamamoto, Tatsuo; Mochizuki, Ryosuke; Uematsu, Takeshi; Fujiwara, Masachika; Ohse, Hirotaka
Abstract : A 21-year-old man, who had been treated for congenital dilatation of the bile duct 13 years previously, presented with an acute abdomen. The physical examination suggested peritonitis, and an emergent laparotomy was performed. A perforation was foundin the jejunum approximately 100 cm distal to the ligament of Treitz, followed by resection of a 60-cm jejunal segment. No tumorous lesions were found during the operation, and the resected jejunal segment showed only focal myxomatous thickening of the serosa. Despite intensive therapy, he died of uncontrollable septic shock 2 days after the operation. Unexpectedly, however, histological examination revealed a liposarcoma, showing an unclassifiable histology. From the distribution of the lesion and the histological findings, it is thought that a primary lesion was somewhere else, covered by severe adhesions due to the previous operation, and that the tumor cells spreading from it could have caused the jejunal perforation through vascular involvement. Although extremely rare, liposarcomas in the abdomen can cause intestinal perforation. It is important for both clinicians andpathologists to carefully investigate the cause of an unusual clinical presentation such as intestinal perforation.